Google BigQuery the Definitive Guide - Lakshmanan, Valliappa; Tigani, Jordan (O'Reilly Media, Inc., 2020)
With Early Release ebooks, you get books in their earliest form-the authors' raw and unedited content as they write-so you can take advantage of these technologies long before the official release of these titles. You'll also receive updates when significant changes are made, new chapters are available, and the final ebook bundle is released. Work with petabyte-scale datasets while building a collaborative, agile workplace in the process. This practical book is the canonical reference to Google BigQuery, the query engine that lets you conduct interactive analysis of large datasets. BigQuery enables enterprises to efficiently store, query, ingest, and learn from their data in a convenient framework. With this book, you'll examine how to analyze data at scale to derive insights from large datasets efficiently. Valliappa Lakshmanan, tech lead on Google Cloud Platform, and Jordan Tigani, engineering director for the BigQuery team, provide best practices in modern data warehousing within an autoscaled, serverless, public cloud. Whether you want to explore parts of BigQuery you're not familiar with, or prefer to focus on specific tasks, this reference is indispensable.